Pengaruh Kualitas Air pada Pertumbuhan Tanaman Bayam Merah - Eko Hartini; Sri Handayani; Eti Rimawati (Dian Nuswantoro Semarang, 2022)
The limited availability of water causes problems in agricultural activities in urban areas. This setting has forced farmers to use polluted river water for crop irrigation. This study aimed to measure the effect of water quality on the growth of red spinach plants. The method employed an experimental with Randomized Block Design (RAK) with three replications, consist of a watering treatment group used river water, filtration water, and well-water. The dependent variables were plant height, number of leaves, dry weight of leaves, and dry weight of roots. The quality of river water and filtered water based on BOD5 and COD parameters has exceeded the class II quality standard as plant irrigation water according to PP No 82 of 2001. However, the well-water was polluted based on the Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017. The plants watered by the river water had the highest number of leaves and tallest plants. In contrast, the dry weight of leaves and roots was highest in plants watered with filtered water. Differences in the source and quality of watering water affect plant height and root dry weight. Applying appropriate water treatment and irrigation technology can obtain significant benefits and minimize risks in river water use.